ANALISIS KEARIFAN LOKAL MASYARAKAT HALMAHERA UTARA UNTUK PENGUATAN KARAKTER MELALUI PEMBELAJARAN BAHASA INDONESIA - Like Suoth; Jefrey Oxianus Sabarua (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to analyze the local wisdom of the people of North Halmahera and its relevance in strengthening students’ character through Indonesian language learning in elementary schools. The research employed a descriptive qualitative approach with an ethnopedagogical perspective. Data were collected through in-depth interviews with traditional leaders, community leaders, and elementary school teachers, participatory observation of cultural practices and oral traditions, as well as documentation studies of folklore and local cultural documents. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing by applying source and technique triangulation to ensure data validity. The findings indicate that the local wisdom of the North Halmahera community is reflected in various cultural forms, such as folklore, customary expressions, mutual cooperation traditions, and social life values. These forms of local wisdom contain character values including religiosity, cooperation, responsibility, honesty, integrity, and respect, which are relevant to the goals of character education and the Pancasila Student Profile. The integration of local wisdom through ethnopedagogy-based Indonesian language learning has the potential to strengthen students’ character, improve language skills, and foster awareness and pride in local cultural identity. This study emphasizes the importance of developing Indonesian language learning strategies that systematically and sustainably integrate local wisdom as an effort to strengthen character while preserving local culture